Leading with questions : how leaders find the right solutions by knowing what to ask - Marquardt, Michael J. (Jossey-Bass, 2014)
How great leaders ask the right questions to get the right results Do people give you the information you need to perform well? Does everyone in your organization understand your vision for the future? Do you know what your boss is really thinking? Do you know that CCL research suggests that the ultimate key to successful leadership is an executive's ability to ask questions and create opportunities for others to ask questions? In this thoroughly updated new edition of his business classic Leading with Questions, internationally acclaimed management consultant Michael Mar.